Conflict-induced behavioural adjustment: a clue to the executive functions of the prefrontal cortex - Mansouri, Farshad A.; Tanaka, Keiji; Buckley, Mark J. (Nature reviews. Neuroscience, 2009)
Key Points In our daily life, we often rely on executive, or cognitive, control processes, which optimize the flexible use of our limited cognitive resources to currently prioritized tasks. Such control may become necessary when automatic or previously learned behaviours can no longer achieve the goal. An experimentally well-studied example of behavioural adjustment in changing environments is the kind of behavioural modulation that is triggered by the presence of competition or conflict between behavioural options. Studying the neural substrate and mechanisms of conflict-induced behavioural adjustment has opened an important window on to the neural basis of executive control. From observations of anterior cingulate cortex (ACC) and dorsolateral prefrontal cortex (DLPFC) activation in tasks that elicited conflict, influential theories have emerged that suggested that the ACC detects the conflict and conveys conflict-related information to areas such as the DLPFC, leading to adjustments in executive-control levels and consequently to better performance when the subject faces the conflict again. Recent studies have revealed striking similarities in conflict-induced behavioural adjustment between humans and monkeys, indicating that monkeys can provide a model to study the underlying neural substrates and mechanisms of such behaviour. Recent studies in humans and monkeys indicate a crucial role for the DLPFC in adaptive and dynamic modulation of executive control, and also suggest involvement of the posterior parietal cortex, the inferior frontal junction area and the cerebellum in conflict-induced behavioural adjustment. However, these studies do not support a causal or indispensable role for the ACC in conflict-induced behavioural adjustment. Models of conflict-induced behavioural adjustment suggest that the anterior cingulate cortex and the dorsolateral prefrontal cortex have specific roles in this process. Mansouri and colleagues discuss and provide an update of these models based on recent human and animal data. The behavioural adjustment that follows the experience of conflict has been extensively studied in humans, leading to influential models of executive-control adjustment. Recent studies have revealed striking similarities in conflict-induced behavioural adjustment between humans and monkeys, indicating that monkeys can provide a model to study the underlying neural substrates and mechanisms of such behaviour. These studies have advanced our knowledge about the role of different prefrontal brain regions, including the anterior cingulate cortex (ACC) and the dorsolateral prefrontal cortex (DLPFC), in executive-control adjustment and suggest a pivotal role for the DLPFC in the dynamic tuning of executive control and, consequently, in behavioural adaptation to changing environments.